TINJAUAN YURIDIS TERHADAP PUTUSAN TINDAK PIDANA PENIPUAN ONLINE TERHADAP LOWONGAN KERJA: Studi Kasus No. Perkara 1470/pid.B/2022/PN Sby - Dirman, Martianus; Cornelis, Vieta Imelda (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The rise of online fraud has now entered an alarming level. To solve this problem, it is necessary to know what are the factors that cause criminal acts of fraud and the efforts made by law enforcement officials in tackling criminal acts of fraud. This research method is Normative Juridical by using secondary and primary data. Factors causing the occurrence of Fraud are influenced by economic, environmental, socio-cultural factors, the ease of committing online fraud crimes, the minimal risk of being caught by the authorities. To prevent crime, preventive measures can be taken, namely carrying out counseling activities, increasing supervision of product sales, and providing appeals through the media. In addition, repressive efforts can be made in the form of prosecution efforts and the application of punishment for perpetrators as well as coaching efforts by correctional institutions. Other efforts that buyers can make are choosing a clear website, looking at pictures and prices carefully, paying attention to payment methods